2016
DOI: 10.1371/journal.ppat.1005606
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating the Plasmodium Sporozoite Surface: Identification of Surface-Exposed Proteins and Demonstration of Glycosylation on CSP and TRAP by Mass Spectrometry-Based Proteomics

Abstract: Malaria parasite infection is initiated by the mosquito-transmitted sporozoite stage, a highly motile invasive cell that targets hepatocytes in the liver for infection. A promising approach to developing a malaria vaccine is the use of proteins located on the sporozoite surface as antigens to elicit humoral immune responses that prevent the establishment of infection. Very little of the P. falciparum genome has been considered as potential vaccine targets, and candidate vaccines have been almost exclusively ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
237
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(255 citation statements)
references
References 89 publications
8
237
0
Order By: Relevance
“…However, the extent of protein N -glycosylation in the blood stages of the parasite seems to be rather low15. Furthermore, the existence of O -glycosylation and C -mannosylation in the parasite has been recently reported for the sporozoite stages16.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extent of protein N -glycosylation in the blood stages of the parasite seems to be rather low15. Furthermore, the existence of O -glycosylation and C -mannosylation in the parasite has been recently reported for the sporozoite stages16.…”
mentioning
confidence: 99%
“…For example UDP-Gal may be required for the synthesis of the α-galactosyl epitopes recently identified in sporozoites20, which seem to be absent in the parasite asexual blood stages21. Similarly, GDP-Fuc could be involved in the posttranslational modification of thrombospondin type I repeat (TSR) domains present in several key proteins of the malaria parasite1622.…”
mentioning
confidence: 99%
“…Furthermore, sporozoites carrying mutations in the putative rhomboid -cleavage site of TRAP exhibit significantly reduced gliding speed in vitro (Ejigiri et al, 2012). Interestingly, recent studies has provided evidence that CSP and TRAP are glycosylated in their thrombospondin type 1 repeat (TSR) domains (Swearingen et al, 2016), further revealing protein modification that is crucial in the design of effective antibody-based vaccines. The putative type 1 transmembrane protein PY01796 (referred to as sporozoites surface protein 3, SSP3), is another protein recently shown to be vital for sporozoites gliding motility.…”
Section: Recent Discoveries In Molecular Targets and Opportunities Avmentioning
confidence: 99%
“…Even so, homologs of several genes required for protein glycosylation are present and conserved in the genomes of Plasmodium spp. and metabolomic analyses of parasite material has demonstrated the presence of the nucleotide sugars required for protein glycosylation, which alluded to the existence of as yet undiscovered parasite glycans.With the aid of modern protein mass spectrometry methods, several research groups have recently tackled the issues of glycan lability and relatively small sample sizes to begin characterizing the true diversity of Plasmodium protein glycosylation [6][7][8][9][10][11][12]. Evidence for the synthesis of short N-linked glycans has been reported in asexual blood stages of Plasmodium falciparum [6], and there is every reason to expect that these modifications will be found in other life cycle stages as well.…”
mentioning
confidence: 99%
“…Evidence for the synthesis of short N-linked glycans has been reported in asexual blood stages of Plasmodium falciparum [6], and there is every reason to expect that these modifications will be found in other life cycle stages as well. Cell surface proteomic studies of P. falciparum and P. vivax sporozoites, the two species responsible for the majority of malaria cases and deaths, have demonstrated that O-and C-linked glycans exist on the essential adhesive proteins, TRAP and CSP [8,10]. These abundant surface proteins are required for parasite infectivity and are prime vaccine candidates because sporozoites represent a population bottleneck in the life cycle as parasites pass from mosquito to human and establish an infection in the liver.…”
mentioning
confidence: 99%